A metal-based tumour necrosis factor-alpha converting enzyme inhibitor1. Issue 19 (7th March 2015) - Leung, Chung-Hang; Liu, Li-Juan; Lu, Lihua; He, Bingyong; Kwong, Daniel W. J.; Wong, Chun-Yuen; Ma, Dik-Lung
<x xml:space="preserve">Abstract</x> We report herein a novel iridium(iii) complex 1 as an antitumour necrosis factor agent and the first metal-based inhibitor of TACE enzymatic activity.